2022
DOI: 10.1109/access.2022.3169503
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Hyper-Heuristics: A Squared Hyper-Heuristic Model for Solving Job Shop Scheduling Problems

Abstract: Hyper-heuristics (HHs) stand as a relatively recent approach to solving optimization problems. There are different kinds of HHs. One of them deals with how low-level heuristics must be combined to deliver an improved solution to a set of problem instances. Literature commonly refers to them as selection hyper-heuristics. One of their advantages is that the strengths of each heuristic can be fused into a highlevel solver. However, one of their drawbacks is that sometimes this generalization scheme does not suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…By performing multiple random samplings in the search space, hyper-heuristic algorithms are able to avoid the trap of local optima, and possess robustness and resilience. Notably, hyperheuristic algorithms have demonstrated successful applications to various combinatorial problems, including the flow shop scheduling problem [26] and container truck routing problem [27]. In light of the specific characteristics of the constructed model, this paper presents a hyper-heuristic algorithm based on a multi-objective simulated annealing algorithm and genetic algorithm.…”
Section: Methodology a Algorithm Selectionmentioning
confidence: 99%
“…By performing multiple random samplings in the search space, hyper-heuristic algorithms are able to avoid the trap of local optima, and possess robustness and resilience. Notably, hyperheuristic algorithms have demonstrated successful applications to various combinatorial problems, including the flow shop scheduling problem [26] and container truck routing problem [27]. In light of the specific characteristics of the constructed model, this paper presents a hyper-heuristic algorithm based on a multi-objective simulated annealing algorithm and genetic algorithm.…”
Section: Methodology a Algorithm Selectionmentioning
confidence: 99%
“…Vela et al 30 used squared hyperheuristics to solve the job shop scheduling problem and demonstrated the exibility of this algorithm. At present, few studies have been performed on the use of the HH framework in the jamming resource allocation problem.…”
Section: Introductionmentioning
confidence: 99%